Risk and progression of dyslipidemia in patients with HIV who have recovered from severe immunosuppression. (June 2009) - Bennett, Matthew T; Bondy, Gregory P
Evaluation of: Williams PL, Wu JW, Cohn SE et al. : Improvement in lipid profiles over 6 years of follow-up in adults with AIDS and immune reconstitution. HIV Med. 10(5), 290––301 (2009). Patients with HIV may develop dyslipidemia and, as such, have an increased risk of developing vascular disease. The causes of HIV-associated dyslipidemia are multifactorial but include the antiretroviral therapy used in its treatment. The study by Williams et al. analyzed the risk of dyslipidemia in patients with HIV who had recovered from severe immunosuppression, a group that has only been previously studied as a subgroup of a larger cohort. In addition, the investigators assessed the effects of long-term antiretroviral therapy, changes in antiretroviral therapy and the addition of cholesterol-lowering medications on the risk of hyperlipidemia and vascular disease in these patients.